2012
DOI: 10.1200/jco.2011.41.3377
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Colorectal Cancer After Detection and Removal of Adenomas at Colonoscopy: Population-Based Case-Control Study

Abstract: Extension of surveillance intervals to 5 years should be considered, even after detection and removal of high-risk polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 38 publications
2
65
0
1
Order By: Relevance
“…At the same time, screening colonoscopy is effective in reducing death from CRC by detection and removal of early polyps [2,3] . Small colonic polyps <10 mm are seldom highly dysplastic [4] and can be routinely removed using a snare or forceps [5] .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, screening colonoscopy is effective in reducing death from CRC by detection and removal of early polyps [2,3] . Small colonic polyps <10 mm are seldom highly dysplastic [4] and can be routinely removed using a snare or forceps [5] .…”
Section: Introductionmentioning
confidence: 99%
“…In line with this hypothesis, large studies show that CRC-related mortality is only slightly increased in patients with high-risk adenomas, even in the context of few surveillance colonoscopies [50]. Moreover, in caseecontrol studies, the risk of developing CRC after removal of adenomas with high-risk features was the same for surveillance colonoscopy at 3 and at 5 years [5], also supporting widening of surveillance intervals.…”
Section: Rationale For Surveillance Intervalmentioning
confidence: 70%
“…However, colonoscopy is an expensive and invasive procedure and surveillance colonoscopy should be targeted at those who are most likely to benefit at the minimum frequency required to protect for cancer [4]. As of today, surveillance colonoscopies have not demonstrated benefit in reducing the incidence or mortality of CRC in randomized controlled trials, but several caseecontrol and cohort studies suggest that follow-up colonoscopy seems to be effective in reducing the risk of CRC among patients with adenomas [5,6]. Besides, the time-intervals for surveillance colonoscopy as recommended by guidelines, are arbitrary and not evidence-based, and next to this, adherence to these guidelines is poor.…”
Section: Introductionmentioning
confidence: 97%
“…All patients had a histologically confirmed first diagnosis of primary CRC and were eligible for recruitment if they were at least 30 years old, physically and mentally able to participate in an interview, sufficiently proficient in German language and resident in the study region. More details about patient recruitment and tissue processing in the DACHS study have been previously reported [17,18]. Of 1975 CRCs diagnosed in 2003-2007 and enrolled in DACHS, 427 had been histologically investigated and TNM classified at the Institute of Pathology, University of Heidelberg, and were included in this study.…”
Section: Study Populationmentioning
confidence: 99%